Investigation of oxidative stress in patients with alopecia areata by measuring the levels of malondialdehyde and ceruloplasmin in the blood - Cwynar, Anna; Olszewska-Słonina, Dorota; Czajkowski, Rafał; Zegarska, Barbara; Białecka, Agnieszka; Męcińska-Jundziłł, Kaja; Piskorska, Elżbieta; Lampka, Magdalena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2018)
Introduction : Alopecia areata (AA) is a chronic, inflammatory and autoimmune disease, presenting with non-scarring hair loss. Although the precise etiopathogenesis of AA remains unknown, oxidative stress is thought to play a role. Aim : To investigate the role of oxidative stress in AA by measuring the levels of plasma and erythrocyte malondialdehyde (MDA) and the ceruloplasmin (CER) in serum. Material and methods : The study included 24 AA patients and a control group consisting of 24 age- and sex-matched healthy volunteers. The levels of MDA and CER were measured and compared between groups. Results : Plasma MDA levels were significantly higher (p < 0.05) in patients with AA compared with controls. No significant difference was observed in MDA erythrocyte levels (p = 0.990) between the study group and the control group. Ceruloplasmin level was higher in the AA group, but this increase was not statistically significant (p = 0.156). Conclusions : Patients with AA displayed significant plasma MDA levels, which could lead to damage in erythrocytes exposed to high concentrations of free radicals. These results demonstrate the presence of an imbalance in the oxidant-antioxidant system and support the concept of a possible role of oxidative stress in AA etiopathogenesis.